‘From the bridge to the Alameda’. Re-percussions and ritornellos in the voice of Lucha Reyes and Pedro Lemebel. - Jarpa Manzur, María del Pilar (Re-presentaciones: Periodismo, comunicación y sociedad, 2022)
From the corpus of Lemebel’s writing to her own transvestite body, the notion of becoming a woman becomes more complex in its transit through cadenced matrices of complicity. Matrices that, while unfolding a multiplicity of figurations of the feminine, do not cease to project differences within ’the difference’. Thus, far from being an empty signifier, the convoluted concept of ’woman’ is nourished by in-corporations that simultaneously invoke and provoke a diversity of alliances with the ’feminine’. Considering a critical gender perspective, this paper seeks to reflect on the musical dimension of these alliances that, in this case, are entwined with the ’voice’ of Lucha Reyes. The complicity that can be glimpsed with this and other female singers opens an attractive field of analysis to explore suggestive lines of flight, through which they are mobilized as referents of old and future irreverence.